An efficient spreadsheet procedure for solving a 0-1 integer programming problem - Machač, Otakar; Böhmová, Simona (Univerzita Pardubice, 2005)
The paper describes a new effective procedure for solving a 0-1 integer optimization problem with use of spreadsheet tables. It is pointed out that a preoptimality analysis plays an important role in these types of problems. Next, the algorithm procedure for use of Microsoft Excel was suggested. It is based on a quick elimination of infeasible combinations and on a reduction of feasible combinations which cannot be the optimal solution for sure. The remaining feasible combinations are analysed in detail in a specifically prepared table in which the optimum solution can be found effectively. In the last part, the advantages of suggested procedure, in comparison with heuristic and exact (used by Solver in Excel) methods, are considered.
Keywords: matematické modelování; Optimalizace; lineární programování; tabulkové procesory